Nutritional Status of Infants and Some Related Risk Factors in Shahroud, Iran - Delvarianzadeh 1, Mehri; Bahar 3, Aysa; Khosravi 2*, Farideh (Shahroud Journal of Medical Sciences, 2018)
Background: This study aimed to assess the nutritional status of children under two years old in two time periods in 1995 and 2016 in rural areas of Shahroud.Methods: This cross-sectional descriptive analytical study enrolled 1443 participants selected by cluster sampling in 1995 and 2016. We calculated the mean standard deviation of weight for age, height for age, and weight for height and compared them with international reference values (WHO/NCHS). The obtained values which were two standard deviations below the mean reference values were defined as wasting, underweight, and stunting. The collected data was analyzed in SPSS software at a significance level of 0.05 using descriptive statistics, chi-square test, and regression analysis.Results: In this study, 1443 children under two years old were studied over two time periods in 1995 and 2016. The results showed 14.9%, 29.5%, and 7.3%, in 1995 and 9.2%, 10.1%, and 4% in 2016 suffered from underweight, wasting, and stunting, respectively. Among the factors involved in malnutrition in 1995 were parents’ education, family size, child gender, birth order, type of the first complementary food, diarrhea, acute respiratory infection in the two weeks prior to the study, and exclusive breastfeeding. In 2016, we observed significant relationships between the body mass index (BMI), underweight, wasting, exclusive breastfeeding, and all three types of malnutrition.Conclusions: Despite a reduction in the prevalence of different types of malnutrition, it is still a common problem. When designing such programs, special attention must be paid to promote breastfeeding.